Grounding the State: Devolution and Development in India's Panchayats - Craig Johnson; Priya Deshingkar; Daniel Start (The Journal of Development Studies, Vol.41, No.6, August 2005, pp.937 - 970, 2005)
Decentralisation is commonly defended on the grounds that it will bring government closer to people, thereby creating political structures that are more transparent and accountable to poor and marginal groups in society. However, a problem that is well recognised in the decentralisation literature is that the devolution of power will not necessarily improve the performance and accountability of local government. Indeed, in many cases, decentralisation simply empowers local elites to capture a larger share of public resources, often at the expense of the poor. Reflecting on these relatively long-standing problems, an important strand of scholarship has argued that central government can play a central role in counterbalancing the forces that tend to disfavour the poor. In this article, we aim to inform this scholarship by reflecting on the interface between local government and local people in two Indian States: Andhra Pradesh (AP) and Madhya Pradesh (MP). Drawing upon 12 months of primary research, we argue that although the government of AP did not devolve power to the extent that proponents of decentralisation would have liked, its populist approach to certain forms of poverty reduction empowered the poor in ways that the more ambitious decentralisation agenda in MP did not. This, we argue, was due in part to the fact that MP's decentralisation process failed to challenge the well-entrenched power of the village chiefs, the sarpanches. But the discrepancy can also be explained in terms of the historical evolution of `development populism' in AP. In particular, we argue that the strong performance of programmes aimed at subsidising rice for low income households and providing credit to women's `self-help groups' (SHGs) was part of the State Government's wider political strategy of enhancing and maintaining electoral support among women, scheduled castes and the poor.